HPV-genotyping versus conventional cervical cytology as a screening method to detect dysplastic cervical epithelial changes - Mahmoud Abbas; Jan de Jonge; Olaf Bettendorf (Scientific Reports, 2022)
Abstract The world health organization (WHO) called for coordinated global action in 2018 to eliminate cervical cancer, ensuring that every woman is screened and treated for precancerous lesions (World Health Organization. Cervical cancer: an NCD we can overcome. Geneva, 2018. http://www.who.int/director-general/speeches/detail/cervical-cancer-an-ncd-we-can-overcome.tegy ). Cytology-based screening has been for decades the conventional method of screening. Ancillary techniques have been added like immunocytochemistry with P16/Ki67 and L1-Capsid, but these methods require maintenance of complex infrastructure and highly trained personnel as well as relatively short screening intervals. HPV-based screening method to detect high-risk groups is a faster and automated method, which does not need morphologically highly qualified personal with high social costs. In the study, we have focused on the distribution of cervical lesions in the age groups with concordance of detection HPV high-risk subtypes (HPV-HR) and on the safety of the screening method. In the Institute for Pathology and Cytology-Schuettorf-Leer-Germany 146.800 samples of women from the age of and above 35 years were analyzed between the beginnings of 2020 until the beginning of 2021. 63.710 cases under 35 years old were analyzed. The samples were processed for both conventional cytological techniques and for molecular detection and subtyping of HPV-HR according to the advice and measurements of BD-manufacture. In this study, we have studied the histopathological results (Table 2) after colposcopy according to the age subgroups. The histopathological results were subdivided into no dysplasia, cervical intraepithelial neoplasia I (CIN I), cervical intraepithelial neoplasia II (CIN II), cervical intraepithelial neoplasia III (CIN III), squamous cell carcinoma (Sq.c.c), adenocarcinoma in situ (AIS), endometrial carcinoma, endocervical adenocarcinoma and cases without biopsy during the colposcopy (COB). We have used the muenchener classification III (Table 3) as a subgrading system for the cytological specimens. The frequency of detecting HPV56/59/66 is higher as detecting HPV-16 and HPV18 in age groups under 35 years old, 41–50 years old and 51–60 years old. HPV16 is detected higher in age groups 35–40 years old and above 60 years. The incidence of high squamous intraepithelial lesions (CIN II and III) is 0.92% in age group 35–40 years, 0.54% in age under 35 years, 0.59% in age group 41–50 years old, 0.35% in age group 51–60 years old and 0.15% in age group above 60 years old. There is no significance (p value = 0.4060). Low grade cervical lesions (CIN I) were 0.13% (< 35 Ys), 0.35% (35–40 Ys), 0.36% (41–50 Ys), 0.25% (51–60 Ys) and 0.098% (> 60Y s), which was statistically significant (p value = 0.04,0.60). Without dysplasia 0.19% (< 35 Ys), 0.5% (35–40 Ys), 0.56% (41–50 Ys), 0.51 (51–60 Ys) and 0.26% (> 60 Ys). There is no significance between occurrence of cervical dysplasia and without dysplasia despite of detection of HPV-HR subtypes (p value = 0.1754). The only use of HPV-subtyping is not a secure method and a protective way for women. There are worldwide many HPV-positive cases, which have been psychologically impaired with higher costs, although they have no cervical epithelial changes during the HPV-infection. There are many HPV-negative cases, in some studies up to 13% of cases, which develop cervical cancer. We have the opinion and are convinced that the screening should be both morphologically via cytological examination and may be with adding immunocytochemistry to detect the really dysplastic cervical lesions. HPV-subtyping may be added every three years to detect the concomitant subtype.